Eco-Friendly Conservation of Yemeni Bronze Artifacts: Efficacy of a KI and Sodium (Z)-4-oxo-4-p-tolyl-2-butenoate Corrosion Inhibitor - Megahed, Mohamed M.; El-Shamy, A. M. (Journal of Environmental Accounting and Management, 2026)
This study explores the conservation and protection of two historically significant bronze artifacts from the Museum of Dhamar, Yemen, which have suffered corrosion due to environmental exposure. To mitigate this degradation, a mixed formula of potassium iodide (KI) and sodium (Z)-4-oxo-4-p-tolyl-2-butenoate was applied as a green corrosion inhibitor. The effectiveness of this eco-friendly solution was evaluated using various analytical techniques, including scanning electron microscopy (SEM), energy-dispersive X-ray spectroscopy (EDX), and electrochemical impedance spectroscopy (EIS). The SEM and EDX analyses revealed a significant reduction in corrosion-related surface damage after treatment, while EIS results confirmed the high inhibitory efficiency of the formula in preventing further corrosion of the bronze artifacts. The study demonstrates that this mixed inhibitor formula not only provides robust protection against corrosion but also offers a sustainable approach to preserving the integrity of cultural heritage artifacts. This research highlights the potential for environmentally friendly corrosion inhibitors to play a critical role in the conservation of metal artifacts exposed to harsh environmental conditions.